Simultaneous quantification of deoxymyoglobin and oxymyoglobin in pork by Raman spectroscopy coupled with multivariate calibration. (15th March 2022) - Li, Huanhuan; Haruna, Suleiman A.; Wang, Yin; Mehedi Hassan, Md; Geng, Wenhui; Wu, Xiangyang; Zuo, Min; Ouyang, Qin; Chen, Quansheng
Highlights: Raman spectroscopic data was successfully acquired. Deoxymyoglobin and oxymyoglobin were effectively measured and quantified. CARS-PLS, GA-PLS and RF-PLS models were executed effectively. The RF-PLS model was most optimum for myoglobin proportions prediction in pork. Abstract: Because of the nutritional advantages and customer acceptance, it is vital to ensure pork meat quality. This study examined the quantification of myoglobin proportions (deoxymyoglobin and oxymyoglobin) by coupling Raman spectroscopy with efficient variables selection chemometrics. Prior to acquiring Raman spectroscopic data, the fractions of myoglobin were determined. Afterward, multivariate calibration methods like partial least square (PLS), competitive adaptive reweighted sampling (CARS-PLS), genetic algorithm-PLS (GA-PLS), and random frog-PLS (RF-PLS) were applied and evaluated. The models' performance was assessed using correlation coefficients of prediction (Rp), root mean square error of prediction (RMSEP), and residual predictive deviation (RPD). The RF-PLS model achieved optimal results for both deoxymyoglobin and oxymyoglobin, with Rp = 0.8936; RMSEP = 2.91 and RPD = 1.97 for the former and Rp = 0.9762; RMSEP = 1.23 and RPD = 4.47 for the latter, respectively. Therefore, this work demonstrated that Raman spectroscopy paired with RF-PLS could be employed for nondestructive, fast, and easy detection of deoxymyoglobin and oxymyoglobin.